Fatal attraction - Mohtarrudin, Norhafizah (Universiti Putra Malaysia Press, 2015)
Seagulls are medium to large birds that survive on live food or scavenge opportunistically. Their morphology allows for equal adeptness in swimming, flying, and walking. Gulls are highly intelligent and highly adaptable to diverse environments. Many species of gull have learned to coexist successfully with humans and have thrived in human habitats.